PERBEDAAN DENYUT JANTUNG DAN TEKANAN DARAH PADA ATLET PREDOMINAN AEROBIK DAN ANAEROBIK KONI JAWA BARAT TAHUN 2016 - Hafiz Aziz; Titing Nurhayati; Nova Sylviana (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2020)
Exercise when done regularly will give big impact to the body. One of the alteration in an athlete that can be made is the cardiovascular system change. This study aimed to discover the difference of heart rate and blood pressure between aerobic predominant athlete and anaerobic predominant athlete. The study design was case-control, data collected from 80 athletes divided into 40 aerobic predominant athletes (canoe, sail, gantole, shooting, and bicycle racing) and 40 anaerobic predominant athletes (weight lifting, taekwondo, softball, tarung derajat, and rock climbing) in KONI West Java, Bandung. Sample was collected by random sampling and analyzed by T test independent. The result showed there was significant difference of heart rate between aerobic predominant athlete and anaerobic predominant athlete (p=0,0001), and lower in aerobic. There was also no significant difference of systolic blood pressure between predominant aerobic athlete and predominant anaerobic athlete (p=0,404), and was higher in anaerobic. Another result showed no significant difference of diastolic blood pressure between predominant aerobic athlete and predominant anaerobic athlete (p=0,553) and was higher in anaerobic. In conclusion, there was significant difference of the heart rate, but no difference of systolic and diastolic blood pressure between aerobic predominant and anaerobic predominant athlete.